Método multicritérios para definição do sistema mais adequado para implantação da manutenção centrada na confiabilidade - Mafra, Vivian (2012)
Nowadays the industrial scenario is presented in intense competition, from that become the reason to have an asset management for high performance. This requires reliability and availability of all plant production systems. At this point the maintenance management function assumes strategic importance for maintaining the stability and productivity of the processes and assets. One of the resources available to maintenance, facing new challenges imposed by the market, is the Reliability Centered Maintenance (RCM). This maintenance management methodology is used to obtain a maintenance plan for physical assets from the application of a structured method in order to establish the best maintenance strategy for a specified system or equipment. This structured method consists of some steps, and among them is the system selection and collecting information that allows you to define which process or equipment shall be first submitted to analysis and implementation of the RCM in order to gain the best benefits. This definition can be done using quantitative methods, qualitative or mixed. This paper proposes a methodology to help determine the priority system for implementation of the RCM.